I am flying into myself : selected poems, 1960-2014 / Bill Knott ; edited by Thomas Lux. - Knott, Bill, 1940-2014 (Farrar, Straus and Giroux, 2017)
A selection of Bill Knott's life work--testimony of his enduring "thorny genius" (Robert Pinsky).